Inter-municipal cooperation in administrative tasks - the role of population dynamics and elections - Ivo Bischoff; Eva Wolfschütz (Philipps-University Marburg, School of Business and Economics, 2019)
We analyze the factors driving the emergence of inter-municipal cooperation (IMC) in tasks of internal administration in West-Germany between 2001 and 2014. In line with the Institutional Collective Action Approach, we find similarities in political ideology to foster cooperation. Cost pressure drives IMC. Given substantial cost hysteresis in administrative tasks, we expect IMC to be more frequent among shrinking municipalities. Our results supports this notion. However, there is no evidence that municipalities make use of complementarities from divergent population dynamics. We apply a hazard model that allows us to analyze the timing of IMC arrangements. We find state subsidies for IMC are an important driving force behind IMC. IMC agreements are less likely to emerge in election years when municipalities face low cost pressure while the opposite is true for municipalities with high cost pressure.
Keywords: H77; D72; 330; Inter-municipal cooperation; public administration; elections; hazard model; Germany; survey